A low turn-on voltage AlGaN/GaN lateral field-effect rectifier compatible with p-GaN gate HEMT technology. (29th January 2021) - Wang, Fangzhou; Chen, Wanjun; Wang, Zeheng; Wang, Yuan; Lai, Jingxue; Sun, Ruize; Zhou, Qi; Zhang, Bo
Abstract: In this paper, we designed a low turn-on voltage ( V On ) AlGaN/GaN lateral field-effect rectifier (LFER) compatible with p-GaN gate high-electron-mobility transistor (HEMT) technology (PG-LFER). We also established an analytical model on the gated control two-dimensional-electron-gas density ( n S ) distributions and V On to investigate the underlying mechanism. The designed PG-LFER features a p-GaN charge storage layer (CSL) under the anode terminal. Net negative charge density in the p-GaN CSL ( σ p-GaN ) is associated with the activated doping concentration of p-GaN CSL ( N p-GaN ) and p-GaN CSL thickness ( t p-GaN ). V On of the PG-LFER is significantly lowered due to the low σ p-GaN caused by reducing the N p-GaN and t p-GaN . Meanwhile, the low V On PG-LFER also preserves recognizable reverse blocking and capacitance characteristics. Verified by the calibrated simulation, the designed PG-LFER shows 70% lower V On compared with the non-optimized LFER with a high σ p-GaN . Compatible with p-GaN gate HEMT technology, the designed PG-LFER with improved performance is a promising candidate for power integrated applications.